95 Injury prevention and law enforcement officers: how partnerships lead to impact. (19th September 2017) - Tiesman, Hope; Rojek, Jeff; Moore, Paul; Alpert, Geoff; Burch, Jim; Montgomery, Brian
Abstract : Introduction: Attention surrounding officer-involved shootings has raised awareness about a range of internal policing issues including use-of-force, discipline of officers, and policing culture, as well as concerns about the overall health and safety of law enforcement officers (LEOs). Recently, law enforcement practitioners, criminologists, and public health researchers combined efforts to consider the impact of police work on the health and safety of LEOs. Approach: NIOSH has partnered with a range of law enforcement stakeholders and these partnerships resulted in the sharing of ideas, resources, and knowledge aimed at improving all aspects of officer safety. Epidemiologic approaches including injury surveillance and the identification of motor vehicle crash (MVC) risk factors paired with criminology approaches including field research and in-depth interviews contributed to three research studies: a case series investigation of fatal MVCs, a quasi-experimental evaluation of an agency crash prevention program, and the collection of non-fatal data on duty-related injuries to officers. Results: Findings from all three studies will be presented. This includes common themes and contributing factors identified by the fatal MVC case series, the interrupted time series results from the quasi-experimental evaluation, and preliminary results from the non-fatal injury study. Our experiences in establishing and maintaining partnerships with the law enforcement community to conduct research and translate findings will also be highlighted. Conclusions: This collective research demonstrates how partnerships can provide the opportunity to respond to the research needs of the law enforcement community. Through these efforts, the development and evaluation of agency-based programs can occur. Significance and Contributions to Injury and Violence Prevention Science: Multi-disciplinary research can positively impact officer safety and health. Tools such as the public health model align with the current research needs of the law enforcement community. Criminology can help epidemiologists better understand police culture to improve both officer and civilian safety.